Beyond will: the empowerment conditions needed to abandon female genital mutilation in Conakry (Guinea), a focused ethnography - Doucet, Marie-Hélène (Reprod Health, 2020)
BACKGROUND: Female genital mutilation (FGM) can give rise to immediate and long-term health problems for girls/women. Numerous studies have identified the sociocultural determinants of this tradition, but so far, in a national context where FGM is highly practiced, virtually none have focused on people refusing to have their daughters cut. We therefore aimed to understand the sociocultural dynamics underlying the non-practice of FGM in Guinea, a country which has one of the most prevalent rates of this practice in the world. This research explored the demographic and sociocultural profiles of Guineans who do not practice FGM, as well as their non-practice experience in a context of high FGM prevalence and social pressure. METHODS: We used a “focused ethnography” methodology and conducted semi-structured individual interviews with 30 women and men from different generations (young adults, parents, grandparents) living in Conakry, Guinea. RESULTS: We found that participants 1) do not disclose their non-practicing status in the same way, and 2) have different experiences with social pressure. A typology was created to describe participants as per their various profiles and experiences, which we named as: 1) the “activists”, 2) the “discrete”, 3) the “courageous”, 4) the “strategists”. DISCUSSION: Wanting to stop practicing FGM is not enough. The main empowering conditions allowing people to enact their decision not to have their daughters undergo FGM are: benefiting from social support (positive social capital), or being financially independent from the traditional solidarity network (sufficient economic capital). We therefore recommend finding ways to increase women’s/families’ empowerment to enact their decision not to practice FGM, mainly by: 1) providing them with new sources of social support, and 2) supporting them to gain more financial independence, including through schooling and improved access to better-paid employment. CONCLUSIONS: This study was the first to explore the experience of people who do not practice FGM in a context of high FGM prevalence and social pressure. The results and recommendations of this research can inform strategies for FGM abandonment and therefore contribute to improving or developing intervention strategies that promote the health and well-being of girls and women.